Adsorption of chlorate from chlor-alkali plant purged brine stream - Lakshmanan, S. (Trans Tech Publications Ltd, 2014)
Coal based activated carbon was found to be able to adsorb chlorate from brine solutions. The removal of chlorate by the activated carbon is enhanced at higher chlorate concentrations, lower temperatures and lower pH. Presence of chlorine in the brine reduces the adsorption of chlorate and is suspected to compete for the same active sites. Chlorate is best removed from de-chlorinated brine. Â© 2014 Trans Tech Publications, Switzerland.